Recent advances in the diagnosis and management of interstitial pneumonia with autoimmune features: the perspective of rheumatologists - Min, Hong Ki (Korean J Intern Med, 2021)
Interstitial pneumonia with autoimmune feature (IPAF) is a recently established disease entity that is comprised of interstitial lung diseases with evidence of autoimmune features but that does not fulfill the criteria for definite autoimmune rheumatic diseases. The classification criteria for IPAF were defined by the European Respiratory Society and American Thoracic Society in 2015. However, further studies to establish IPAF subgroups and treatment modalities for each subgroup are still needed. In this review, we discuss recent advances regarding IPAF and raise critical points for the diagnosis and management of patients with IPAF from the perspective of rheumatologists.